Effect of exchange rate, nflation, interest rate, and net profit on stock price index combined (IHSG) - Mutiara Angelica Simanjuntak; Ellen A Simanjuntak; Wirda Lilia; Rafiqah Humira (Institute of Computer Science (IOCS), 2023)
This study was designed to assess the Composite Stock Price Index in banking sub-sector financial companies listed on the Indonesia Stock Exchange from 2018 to 2021, whether they can be influenced by exchange rates, inflation, interest rates, and net income. The information used is obtained from annual reports on the Indonesia Stock Exchange website https://www.idnfinancials and is selected based on established standards. A total of 47 banking companies were used as the study population with 68 samples. This study intends to advance knowledge that will be useful not only for current researchers but also students and the general public who are looking for sources of information. The results of this study indicate that the variable is related to the exchange rate which has a partial and significant positive effect on the JCI, while inflation and interest rates have neither a positive nor a significant effect. Finally, net profit has a partial, but significant, negative effect on the JCI